Efeito dos lasers vermelho e infravermelho sobre a ativa????o das c??lulas respons??veis pelo direcionamento do reparo muscular - Almeida, Terezinha Aparecida de (2015)
Interactions between the muscle and macrophages which invade it after an injury occurs are crucial to the evolution of repair in this tissue. On the other hand, low intensity laser (LLLT) has long been used in the treatment of such lesions, both in clinical and experimental settings; however, little is known about its effects on macrophages. The objective of this project was to evaluate the effect of irradiation with red and infrared laser on the activation state of M1 and M2a phenotypes of macrophages. For this purpose, J774 macrophage cultures were treated with polarizing agents (LPS and IFN-y or IL-4) for 24 hours and were then irradiated with 2 wavelengths of LLLT ??? 780 nm and 660 nm ??? in the same dosimetric parameters (70mW; 17.5J/cm2; 0.8J). After 24 hours of incubation, the activation state was checked by MTT technique. In each experimental situation, non-irradiated cells served as controls, and three independent experiments were performed. Laser irradiation with 780 nm proved able to decrease the activation of macrophages polarized for M1 phenotype and increase activation of M2a profile macrophages. Laser irradiation with 660 nm slightly intensified the state and activation of M1 macrophages, while significantly increasing the activation state of M2a profile macrophages. Although it is not possible to establish a relationship between the results of in vitro studies and future clinical outcomes, and the effects of laser irradiation on other macrophage phenotypes still need to be assessed, data from this study suggest that red and infrared laser could have different results when used in the different stages of muscle repair.